I can tell my "story"! - Angela Dirce Vieira Mangliocca; Daniela Amélia Martins Constantino (Universidade Federal de Santa Catarina, 2009)
The considerations described here arise due to the training project, developed in the nursery Waldemar da Silva Filho due to the discipline of Supervised Internship in Child Education Course Pedagogia / UFSC, in the period 2008 / 2 and 2009 / 1.